Open charm production and asymmetry in pNe collisions at √sNN = 68.5 GeV - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (The European physical journal. C, Particles and fields, 2023)
A measurement of D 0 meson production by the LHCb experiment in its fixed-target configuration is presented.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 08.01.2024
LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, B. Leverington, J. Marks, R. Skuza, D. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]